Self-adaptive Equilibrium Optimizer for solving global, combinatorial, engineering, and Multi-Objective problems - Houssein, Essam H.; Çelik, Emre; Mahdy, Mohamed A.; Ghoniem, Rania M. (Expert systems with applications, 2022)
This paper proposes a self-adaptive Equilibrium Optimizer (self-EO) to perform better global, combinatorial, engineering, and multi-objective optimization problems. The new self-EO algorithm integrates four effective exploring phases, which address the potential shortcomings of the original EO. We validate the performances of the proposed algorithm over a large spectrum of optimization problems, i.e., ten functions of the CEC’20 benchmark, three engineering optimization problems, two combinatorial optimization problems, and three multi-objective problems. We compare the self-EO results to those obtained with nine other metaheuristic algorithms (MAs), including the original EO. We employ different metrics to analyze the results thoroughly. The self-EO analyses suggest that the self-EO algorithm has a greater ability to locate the optimal region, a better trade-off between exploring and exploiting mechanisms, and a faster convergence rate to (near)-optimal solutions than other algorithms. Indeed, the self-EO algorithm reaches better results than the other algorithms for most of the tested functions. •An enhanced algorithm called the self-EO that employs three strategies is proposed.•Self-EO efficiency and performance are verified on several benchmarks.•CEC’20 suite and 3 engineering problems are used for algorithm validation.•Two combinatorial problems, and ten CEC’20 multi-objective problems are solved.•Self-EO performance is analyzed with many metrics and compared to 30 algorithms.